2013
DOI: 10.1039/c3an36788f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of microRNA-21 based on bio bar code and hemin/G-quadruplet DNAenzyme

Abstract: A simple and novel microRNA (miRNA) biosensor was developed using DNA-Au bio bar code (DNA-Au) and G-quadruplex-based DNAenzyme. DNA-Au increased the amount of miRNA-21 participating in hybridization. Hemin/G-quadruplex DNAenzyme significantly improved the catalysis of H(2)O(2) by oxidation of hydroquinone, resulting in an obvious reduction current of benzoquinone for miRNA-21 indirect detection. Under optimum conditions, the linear relationship between miRNA-21 concentration and reduction response was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Strategies to induce a change in charge transfer include the enzymatic turnover of an insulating polymer via DNAzymes, 143 hemin conjugated carboxylic graphene 144 and DNAzyme functionalized gold nanoparticles 145 . These assays reported detection limits ranging from 100s of aM to 10 of fM LODs with dynamic ranges of 1.5, 3.5, and 4.5 orders, respectively.…”
Section: Biosensor Methodsmentioning
confidence: 99%
“…Strategies to induce a change in charge transfer include the enzymatic turnover of an insulating polymer via DNAzymes, 143 hemin conjugated carboxylic graphene 144 and DNAzyme functionalized gold nanoparticles 145 . These assays reported detection limits ranging from 100s of aM to 10 of fM LODs with dynamic ranges of 1.5, 3.5, and 4.5 orders, respectively.…”
Section: Biosensor Methodsmentioning
confidence: 99%
“…Three kinds of tumor cell lines (A549, HepG2 and MCF-7) with high miRNA-21 expression levels (Calin et al, 2004;Iorio et al, 2005;Wang et al, 2011;Meng et al, 2013) are selected to investigate the capacity of our method for detection of tumor cells. Different concentrations of cells confirmed by cell counting range from 10 2 cells to 10 6 cells, were treated by the total RNA extraction kit, and then followed by EFA and fluorescence detection.…”
Section: Detection Of Mirna-21 Expression Levels In Different Tumor Cmentioning
confidence: 99%
“…A detection limit of 3.96 pM and a dynamic range of 5 pM–5 nM were obtained. Furthermore, they found that the hemin-G-quadruplex on AuNPs can significantly promote the catalysis of H 2 O 2 by oxidation of hydroquinone; this led to an obvious reduction current of benzoquinone [38]. This method could be used to detect miRNAs with a detection limit of 6 fM and a dynamic range of 0.01–500 pM.…”
Section: Nanomaterials-based Electrochemical Strategies For Mirnasmentioning
confidence: 99%